MID-TRIMESTER UTERO PLACENTAL DOPPLER ARTERIAL ULTRASOUND STUDY AS INDICATOR OF ADVERSE OBSTETRIC OUTCOME IN HIGH –RISK PREGNANCY - Ahmed Al hialy, Hadeel Mohamed Farook (International Journal of Psychosocial Rehabilitation, 2020)
The objective f this study was to evaluate utero artery Doppler ultrasound efficiency in adverse pregnancy outcome prediction among high-risk pregnant women in Mosul city. where 60 pregnant women who were high risk for development of preeclampsia, placenta abruption, low weight of the born were selected and early labor during their pregnancy, and Doppler ultrasound was conducted for these women in 18-24 gestational weeks to assess utero artery notching. In this study notching was defined as the lack of diastolic flow in utero artery waves. The patients were distributed into two groups: (Group A, n= 27) represented women who hadnotch , (Group B n=33) represented women who had didn't had notch.The study concluded many results from them: The weight of the new born in Groups A and B was 2091and 3025 gm, respectively. In our study, 11cases were delivered before 37 weeks (early labor). Preeclampsia, placenta abruption, and low weight of the born were significantly higher in the group (A ) other than group (B), but there is no significant differences regarding early labor the two groups. Based on the results, utero artery ultrasound had high NPV in predicting of preeclampsia, abruption, and low weight of the born, thus evaluate presence or absence of notching in mid-trimester by using utero artery ultrasound for high-risk pregnant ladies could enhance the outcome adverse obstetric outcome. So the current study recommends Doppler ultrasound usage in high-risk pregnancy cases in mid-trimester for pregnancy outcome prediction.